2015
DOI: 10.3390/e17106834
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Change of Signal Complexity in the Brain During Inhibitory Control Processes

Abstract: Abstract:The ability to inhibit impulses and withdraw certain responses are essential for human's survival in a fast-changing environment. These processes happen fast, in a complex manner, and require our brain to make a fast adaptation to inhibit the impulsive response. The present study employs multiscale entropy (MSE) to analyzing electroencephalography (EEG) signals acquired alongside a behavioral stop-signal task to theoretically quantify the complexity (indicating adaptability and efficiency) of neural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…However, some studies using clinical applications have suggested the parameters of m = 1 or 2 and r = 0.1 to 0.25 to provide a high validity for sample entropy in EEG signals (e.g., Escudero et al, 2006 ; Takahashi et al, 2009 ; Yang et al, 2013 ). With these suggested parameters we have also obtained good results in the past when analyzing EEG signals in the context of cognitive tasks similar to the current study ( Wang et al, 2014 ; Huang et al, 2015 ). Specifically, in this study the pattern length, m , was set to 1 (i.e., one data point was used for pattern matching).…”
Section: Methodssupporting
confidence: 72%
See 3 more Smart Citations
“…However, some studies using clinical applications have suggested the parameters of m = 1 or 2 and r = 0.1 to 0.25 to provide a high validity for sample entropy in EEG signals (e.g., Escudero et al, 2006 ; Takahashi et al, 2009 ; Yang et al, 2013 ). With these suggested parameters we have also obtained good results in the past when analyzing EEG signals in the context of cognitive tasks similar to the current study ( Wang et al, 2014 ; Huang et al, 2015 ). Specifically, in this study the pattern length, m , was set to 1 (i.e., one data point was used for pattern matching).…”
Section: Methodssupporting
confidence: 72%
“…For example, using a stop-signal task that is designed to induce inhibitory control mechanism, studies have shown that people who are better able to suppress a motor response tend to show higher EEG complexity in MSE analysis. This is true in between-subject studies ( Huang et al, 2015 ), as well as within-subject studies where the same participants’ EEG signals are measured pre- and post-intervention ( Liang et al, 2014 ). In a VSTM study, Wang et al (2014) also showed that physically active elderly adults had higher EEG signal complexity compared to their sedentary counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is based on the assumption that (1) high-performers already possess an optimally amount of variability, or complexity 55 , in their endogenous neural signals, and (2) theta tACS with fixed phase envelope is too monotonous and thus eliminates such intrinsic signal variability. Indeed, it has been reported that high-performers in cognitive tasks tend to exhibit more complex neural signals 56 (via entropy) than low-performers 57 , and using tACS to boost phase-locking may sometimes be detrimental to WM performance 58 . Looking closer at our results, we speculate that perhaps the optimal phase difference for our task may be somewhere between 0° and 90°, hence why a tACS phase difference of 0° was able to pull low-performers closer to the ballpark and improve their VWM, but a tACS phase of 180° could impair high-performers already-accurate phase relationship more so than the 0° condition.…”
Section: Discussionmentioning
confidence: 99%